2021
DOI: 10.3389/fcell.2021.601600
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cell-Derived Exosomes Regulate Neural Stem Cell Differentiation Through miR-9-Hes1 Axis

Abstract: Exosomes, a key element of the central nervous system microenvironment, mediate intercellular communication via horizontally transferring bioactive molecules. Emerging evidence has implicated exosomes in the regulation of neurogenesis. Recently, we compared the neurogenic potential of exosomes released from primary mouse embryonic neural stem cells (NSCs) and astrocyte-reprogrammed NSCs, and observed diverse neurogenic potential of those two exosome populations in vitro. However, the roles of NSC-derived exoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 60 publications
2
64
1
Order By: Relevance
“…14,15 These miRNAs in EVs significantly promote neurogenesis in vitro. 14,15 These findings implied the importance to examine the involvement of iNPC-EVcontaining miRNAs in the regulation of cell survival, which is under investigation. In summary, our study identified EVs as an essential element of iNPC-mediated modification of microenvironment and provided new evidence for the inextricable crosstalk between cell extrinsic and intrinsic factors in regulating NPC survival.…”
Section: Induced Neural Progenitor Cell-derived Extracellular Vesicles Promote Neural Progenitor Cell Survival Via Extracellular Signalrementioning
confidence: 98%
“…14,15 These miRNAs in EVs significantly promote neurogenesis in vitro. 14,15 These findings implied the importance to examine the involvement of iNPC-EVcontaining miRNAs in the regulation of cell survival, which is under investigation. In summary, our study identified EVs as an essential element of iNPC-mediated modification of microenvironment and provided new evidence for the inextricable crosstalk between cell extrinsic and intrinsic factors in regulating NPC survival.…”
Section: Induced Neural Progenitor Cell-derived Extracellular Vesicles Promote Neural Progenitor Cell Survival Via Extracellular Signalrementioning
confidence: 98%
“…As an alternative therapy, extracellular vesicles (EVs), which play a key role in intercellular communication through the transmission of unique molecular signatures, have been proposed [ 16 ]. Stem cell-derived EVs are from cells of origin that can regulate tissue regeneration [ 17 , 18 ]. In particular, hypothalamic NSC-derived exosomes significantly slow senescence-mediated NSC loss through exosomal miRNA delivery [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies report the relevance of neural cell-derived sEVs to be used in neurodegenerative conditions ( Huo et al, 2021 ). The direct conversion of somatic cells into induced neural precursor cells (iNPCs) provides abundant production of sEVs ( Ma et al, 2019 ; Yuan P. et al, 2021 ), mainly if using bioreactors ( Baghbaderani et al, 2011 ; Miranda et al, 2016 ). These sEVs after transplantation revealed to have therapeutic properties in ischemic stroke ( Zhang et al, 2020 ).…”
Section: Biogenesis Production and Storage Of Sevsmentioning
confidence: 99%